English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

pls also try this... (tanx/1-cotx) + (cotx/1-tanx) = 1 + tanx - cotx

2006-12-04 18:31:18 · 4 answers · asked by justanasker 1 in Science & Mathematics Mathematics

4 answers

Not sure bout the first one but I got the second one:( I think yur RHS shud be "1+tanx+cotx"

tanx/[1-(1/tanx)] +cotx/(1-tanx)
= (tanx)(tanx)/tanx-1 +cotx/(1-tanx)

=tanx(tanx)/tanx-1 - cotx/tanx-1

={[tanx(tanx)] - cotx}/ tanx- 1

its really hard to write the rest down so I'll try and explain it. So u got "[tanx(tanx)] - cotx"
the whole divided by "tanx -1"
u write "cotx" as '1/tanx' . then u'll get

=tanx(tanx)(tanx) - 1/ (tanx-1)tanx

the numerator is in the form of the identity (a3-b3) = (a-b)(a2+ab+b2)

u expand it and get
(tanx-1)(tanx2 +tanx +1) / (tanx-1)tanx

= tan2x +tanx+1/ tanx

divide each term of the numerator by "tanx " and you get
"1 +tanx + cotx"

Im sorry its hard to understand but hope u got sumthin :)

2006-12-04 19:01:11 · answer #1 · answered by Lynne 4 · 0 0

(secx-tanx)^2+1
= Secx^2 - 2.secx.tanx + Tanx^2 + 1
[ Tanx^2 + 1 = Secx^2 ]

= 2Secx^2 - 2.Secx.tanx
=2Secx [ Secx - Tanx]


Therefore the EQuation u gave BEcomes

2Secx [ Secx - tanx ] / [Secx - Tanx ]

= 2Secx

As LHS = RHS Hence Proved



Signing off.... Vivek

2006-12-04 18:53:07 · answer #2 · answered by vedic_vivek 1 · 0 0

1)LHS=(secx-tanx)² + 1 / secx-tanx
We know that sec²x - tan²x=1
Substitute this in the numerator

=>[(secx - tanx)² + (sec²x - tan²x)]/secx-tanx
=>[(secx - tanx)² + (secx - tanx)(secx + tanx)]/secx-tanx
taking (secx-tanx ) comman in the numerator

=>(secx-tanx) [secx-tanx + secx + tanx]/secx-tanx
=>2secx=RHS
Hence proved.

2)LHS=(tanx/1-cotx) + (cotx/1-tanx)
put cotx=1/tanx

=>tanx/(1-1/tanx) + (1/tanx)/(1-tanx)
=>tan²x/(tanx - 1) + 1/[(1-tanx)tanx]

taking LCM
=>[-tan²x(tanx) + 1]/(1-tanx)tanx
=>[1-(tanx)^3]/(1-tanx)tanx
now a^3 - b^3 =(a-b)(a^2 + b^2 + ab)

=>(1-tanx)(1+ tan²x + tanx)/(1-tanx)tanx
=>(1+tan²x + tanx)/tanx
=>cotx + tanx +1

=>The RHS term given by you is wrong, the correct form is as calculated!

LHS, RHS denote left hand side, right hand side

2006-12-05 01:12:45 · answer #3 · answered by sushant 3 · 0 0

sec^2x+tan^2x-2secxtanx+1/(secx-tanx)

As 1+tan^2x=sec^2x, replacing it in the above equation

sec^2x+sec^2x-2secxtanx/(secx-tanx)

2sec^2x-2secxtanx/(secx-tanx)

2secx(secx-tanx)/(secx-tanx)

2secx

2006-12-04 19:24:03 · answer #4 · answered by raghunandan r 1 · 0 0

fedest.com, questions and answers